Data gathering maximisation for wireless sensor networks with a mobile sink. (21st October 2019) - Han, Zongyuan; Shi, Tianyun; Lv, Xiaojun; Jia, Xinchun; Wang, Zhongying; Zhou, Dong
Recent studies have demonstrated that the significant benefit can be achieved by using mobile sinks for data gathering in wireless sensor networks (WSNs). However, most of them employed a typical scheme that the mobile collector pauses at the anchor points on its moving tour for a period time to collect the data from nearby sensors. In this paper, the data gathering process is divided into two stages named parking communication (PC) and moving communication (MC). We focus on maximising the total amount of data gathering by the mobile sink, and formulate the problem as two different optimisation models under several constraints for these two different communication stages. Accordingly, dual decomposition and simplex methods are dexterously exploited to derive the optimal communication time and flow rates allocation schemes. Computational results demonstrate the efficiency of the proposed algorithms.